Evaluation of rating curves for some gauging stations in Sarawak - Zuhailah, Taib (University Malaysia Sarawak, UNIMAS., 2005)
The purpose of this project is to evaluate rating curve equation for some gauging stations in Sarawak. In order to carry out this project, four gauging stations have been selected; Asa Jaya (Samarahan Basin), Bedup (Sadong Basin), Entebar (Lupar Basin) and Samu (Saribas Basin).